Pembuatan alat ukur sudut datang dan intensitas cahaya matahari real time menggunakan sensor accelerometer dan LDR (Measuring instrument fabrication of incidence angle and real-time sunlight intensity using accelerometer and LDR sensors measuring instrument) - Ocha Samantha Feriyana; Zulhendri Kamus (Department of Physics – Universitas Negeri Padang UNP, 2019)
This research aims to determine the accuracy and accuracy of the measuring instrument of the angle of arrival and the intensity of sunlight in real time using an accelerometer sensor and LDR. . To achieve this goal, R & D research was conducted which consisted of: reviewing existing tools, conducting literature studies, planning tool development, internal testing of tool design, revision of tool design, limited testing of measuring instruments, revision of measuring instruments and field trials main. Data were analyzed using calculations to find out the accuracy of measurements. The results of data analysis explain two important things from making a measuring instrument system. First, the angle of view measuring instrument and the intensity of sunlight consist of an accelerometer sensor and LDR. Measurement data is displayed on the LCD. Second, the accuracy and accuracy of the measuring instrument. In the measurement results, the azimuth values obtained from the measuring instrument are compared with the data obtained from BMKG. From the results of these comparisons, the average percentage of accuracy and error in measuring instruments is 95.5% and 4.52%. In the sun light intensity, the results of data analysis showed that the accuracy and error measurement of light intensity were 92.83% and 7.17% respectively.